2018
DOI: 10.1155/2018/8727301
|View full text |Cite
|
Sign up to set email alerts
|

Alexis Wound Retractor for Radical Cystectomy: A Safe and Effective Method for Retraction

Abstract: Surgical site infection rates remain a common postoperative problem that continues to affect patients undergoing urologic surgery. Our study seeks to evaluate the difference in surgical site infection rates in patients undergoing open radical cystectomy when comparing the Bookwalter vs. the Alexis wound retractors. After institutional review board approval, we performed a retrospective chart review from February 2010 through August 2017 of patients undergoing open radical cystectomy with urinary diversion for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Various studies in which the Alexis ® retractor was compared with metal retractors during gastrointestinal surgery showed that Alexis ® wound retractor was more effective in preventing SSI. 18,20,21,22 Nevertheless, this apparent usefulness of Alexis ® retractors during abdominal surgery was not consistent across wound assessments performed by clinicians and those reported by patients post laparotomy, where it was asserted that wound edge protection devices do not reduce the rate of SSI at all. 23…”
Section: Discussionmentioning
confidence: 98%
“…Various studies in which the Alexis ® retractor was compared with metal retractors during gastrointestinal surgery showed that Alexis ® wound retractor was more effective in preventing SSI. 18,20,21,22 Nevertheless, this apparent usefulness of Alexis ® retractors during abdominal surgery was not consistent across wound assessments performed by clinicians and those reported by patients post laparotomy, where it was asserted that wound edge protection devices do not reduce the rate of SSI at all. 23…”
Section: Discussionmentioning
confidence: 98%